Is tranexamic acid use in patients with a hip fracture safe?: a consecutive cohort study based on complete follow-up in a national database. (1st March 2021) - Viberg, Bjarke; Gundtoft, Per Hviid; Schønnemann, Jesper Ougaard; Pedersen, Lasse; Andersen, Lis Røhl; Titlestad, Kjell; Madsen, Carsten Fladmose; Clemmensen, Signe Bedsted; Halekoh, Ulrich; Lauritsen, Jens; Overgaard, Søren
Abstract : Aims: To assess the safety of tranexamic acid (TXA) in a large cohort of patients aged over 65 years who have sustained a hip fracture, with a focus on transfusion rates, mortality, and thromboembolic events. Methods: This is a consecutive cohort study with prospectively collected registry data. Patients with a hip fracture in the Region of Southern Denmark were included over a two-year time period (2015 to 2017) with the first year constituting a control group. In the second year, perioperative TXA was introduced as an intervention. Outcome was transfusion frequency, 30-day and 90-day mortality, and thromboembolic events. The latter was defined as any diagnosis or death due to arterial or venous thrombosis. The results are presented as relative risk (RR) and hazard ratio (HR) with 95% confidence intervals (CIs). Results: A total of 3, 097 patients were included: 1, 558 in the control group and 1, 539 in the TXA group.31% (n = 477) of patients had transfusions in the control group compared to 27% (n = 405) in the TXA group yielding an adjusted RR of 0.83 (95% CI 0.75 to 0.91). TXA was not associated with increased 30-day mortality with an adjusted HR of 1.10 (95% CI 0.88 to 1.39) compared to the control group as well as no association with increased risk of 90-day mortality with a per protocol adjusted HR of 1.24 (95% CI 0.93 to 1.66). TXA was associated with a lower risk of thromboembolic events after 30 days (RR 0.63 (95% CI 0.42 to 0.93)) and 90 days (RR 0.72 (95% CI 0.52 to 0.99)). A subanalysis on haemoglobin demonstrated a median 17.7 g/L (interquartile range (IQR) 11.3 to 27.3) decrease in the control group compared to 17.7 g/L (IQR 9.7 to 25.8) in the per protocol TXA group (p = 0.060 on group level difference). Conclusion: TXA use in patients with a hip fracture, was not associated with an increased risk of mortality but was associated with lower transfusion rate and reduced thromboembolic events. Thus, we conclude that it is safe to use TXA in this patient group. Cite this article: Bone Joint J  2021;103-B(3):449–455.